Comparative Analysis of Experimental and Numerical Investigation on Thermophysicalproperties in Hydro Carbon Mixtures using Jouyban-Acree Model at Various Temperatures - R., Ramesh; T. K., Thanusha; K., Ramesh; M. Y. M., Yunus (Asian Research Publishing Network (ARPN), 2016)
The thermophysical properties of liquid mixtures provide additional information regarding molecular interactions. A perusal of the literature revealed that the predictions of thermophysical properties of liquid mixtures are scarce. With an aim, the thermophysical properties of viscosity, excess molar volume VE and viscosity deviations Δη of liquid mixtures are predicted by using various nonlinear models. In this reseach Jouyban-Acree viscosity models have been used for predicting viscosity of Acetophenone with P-xylene and 1, 4 Dioxane with Benzene at different mole fractions measured at various temperatures in the atmospheric pressure condition. From experimentation excess volumes, VE, and deviations in viscosities, Δη, of mixtures at infinite dilutions have been obtained. The measured systems show positive VE and negative Δη with increasing temperatures. From the positive excess molar volume, when aromatics, which exist in a highly associated form in the pure state, are mixed with polar solvents (ketones), the monomerization occurs and new specific interactions appear in the solution.The negative viscosity deviation depends on the size and shape of the molecules and molecular interactions. These measured data tailored to the Jouyban-Acree nonlinear models to derive the binary coefficients Jouyban-Acree model is more adequate for the thermo physical and the standard deviation was found to be < 2.06 %. The molecular interactions existing between the components and comparison of liquid mixtures were also discussed.